İşyerinde Psikolojik Tacizin Türk Ceza Hukukundaki Yeri - Uysal, Fadim Tuğba (Fatih Sultan Mehmet Vakıf Üniversitesi, 2023)
Çalışanlar üzerinde belirli bir süre devam ederek çalışanları yıldıran, işyerinden uzaklaştıran işyerinde psikolojik taciz davranışları Türk Ceza Kanunu bakımından bu tezin konusunu oluşturmaktadır. Tez üç ana bölümden oluşmaktadır. İlk bölümde işyerinde psikolojik tacizin tanımı, tarihsel gelişimi, sebepleri ve sonuçları incelenmektedir. İkinci bölümde uluslarası hukukta işyerinde psikolojik tacizle mücadele kapsamında yapılan yasal düzenlemelere yer verilmiştir. Son bölümde ise işyerinde psikolojik taciz fiilleri yürürlükte bulunan Türk Ceza Kanunu’nda bulunan benzer suç tipleri kapsamında incelenmektedir. Böylelikle yeni yasal bir düzenlemeye ihtiyaç olup olmadığı görüşlerimiz ile irdelenmiştir.

Psychological harassment behaviors in the workplace, which continue for a certain period of time, intimidate employees and drive them away from the workplace, constitute the subject of this thesis in terms of the Turkish Criminal Code. The thesis consists of three main chapters. The first chapter examines the definition, historical development, causes and consequences of psychological harassment at the workplace. In the second part, the legal regulations in international law within the scope of combating psychological harassment in the workplace are given. In the last part, the acts of psychological harassment in the workplace are examined within the scope of similar types of crimes in the Turkish Criminal Code in force. Thus, whether there is a need for a new legal regulation is examined with our opinions.
The Place of Psychological Harassment at Work' in Turkish Criminal Law
Keywords: Mobbbing; İşyerinde Şiddet; İşyerinde Psikolojik Taciz; Yıldırma; Zorbalık; Mobbing; Workplace Violence; Psychological Harassment at Workplace; Intimidation; Bullying